Studi Ekologi Hutan Mangrove di Kota Waisai Kabupaten Raja Ampat, Papua Barat - Efradus H. Mirino; Suriani Br. Surbakti; Lisye I. Zebua (Jurnal Biologi Papua, 2014)
This aim of the research is to know the condition of the ecology of mangrove forests in the Waisai Raja Ampat District, West Papua. This research was carried out during the year, from April 2012-April 2013. Research locations include three (3) stations which were Moko, Kimindores and the tourist port area. The method was line transect with quadratic plot along a 100-meter at the seaside. The plots were created in size of 1 x 1m2; 5 x 5 m2; 10 x 10 m2 and 20 x 20 m2. The observations showed that there were 8 types of mangrove in the town of Waisai consisting of Avicennia officinalis, Sonneratia alba, Rhizophora stylosa, R. mangle, R. mucronata, Aegricecas floridum, Bruguiera gymnnorhiza, and Nypa fruticans. The distribution of mangrove types in Waisai is spread unevenly. A. floridum was found only at Moko; R. mucronata was at  the area of the tourist Port only; and Nypa has a wider distribution since they were found at the three stations of observations. Key words: biota, diversity, mangrove, Raja Ampat.